Concrete repair for building maintenance work / Noor Saadiah Bidin - Bidin, Noor Saadiah (Faculty of Architecture, Planning and Surveying, 2009)
Concrete is made up of three basic components which are water, aggregate (rock, sand or gravel) and Portland cement. Cement usually in a powder form, act as a binding agent when mixed with water and aggregates. This combination or concrete mix will be poured and harden into the durable material with which we are all familiar. Concrete is a versatile building material that is cast inexpensively and is durable, strong and takes the shape of the form in which it is cast. Most concrete members are cast on site and in their final location. Marginal works and construction procedures cause imperfections that required repair. Natural forces and use in service cause deterioration or damage which must be repaired or replaced during maintenance of the structure. The choice of a repair material must consider thermal compatibility with the base concrete, durability requirements, service conditions, chemical and electrical environment, shrinkage characteristics, modulus elasticity and placement conditions. Most concrete repairs involve the removal of concrete which may either have deteriorated or have a construction defect or be damaged. There are various methods of removal and repair which are economic, safe and easy which suitable with the concrete damage or crack.